Comparative investigation of fractional bioconvection and magnetohydrodynamic flow induced by hybrid nanofluids through a channel - Raza, Ali; Nigar, Niat; Khan, Umair; Elattar, Samia; Eldin, Sayed M.; Abed, Ahmed M. (Frontiers in Materials, 2023)
In accordance with a notable discovery, the functional effects of medications, such as those that slow down and calm the body, may be investigated for the polarized diffusion coefficient based on the subsequent increase throughout magnetism. This study inspects the impact of an applied magnetic field on a naturally occurring Brinkman- type flow of a viscous and incompressible hybrid nanofluid over two parallel plates. Water and sodium alginate are supposed as the base fluids, with titanium dioxide (TiO2) and mercury (Ag) as the two nanoparticles, along with their physical properties. With the help of Laplace transformation, the transformed fractional model is investigated using the recent definitions of fractional-order derivatives with memory effect, i.e., Atangana-Baleanu (AB) and Caputo-Fabrizio (CF) fractional derivatives. Different limitations' effects on various nanoparticles are examined and visually shown graphically. As a result, we have discovered that the improvement in volumetric fraction regulates the fluid velocity by making it travel more slowly. Furthermore, due to the physical properties of the studied nanoparticles and base fluids, the water-based hybrid nanofluid has a more significant influence on the temperature and momentum profile than the sodium-alginate based hybrid-nanofluid. Moreover, the velocity profile has a more significant value for the AB-fractional derivative rather than the CF-fractional derivative due to the memory effect.